(untitled) (Research, Society and Development, 2022)
Objective: To describe the care and management changes experienced by nurses in the face of COVID -19. Methodology: This is a descriptive, cross-sectional study with a qualitative approach, with 20 nurses from a teaching hospital in the interior of Minas Gerais, between January and July 2022, through a virtual questionnaire, afterwards, discourse analysis was carried out of the collective subject. Results: Two categories correspond to the objective: nursing care and managerial changes: the need for professional training during the COVID -19 pandemic and challenges in the organization of the nursing work process - structural, people, and human resources. The COVID-19 crisis period reinforces the development of nurses in skills, abilities, and managerial attitudes, to articulate and integrate health actions at all levels of hospital health care. Conclusion: Nurses showed consistency in assignments from management to assistance to care management that directly impact the entire health organization, especially sectors, teams, and patients.